Ancient Manuscript Preservation of Museum Ranggawarsita Library Collection Semarang Central Java - Khafidlin, Khafidlin (Daluang: Journal of Library and Information Science, 2021)
Introduction: This article “Ancient Manuscript Preservation of Museum Ranggawarsita Library Collection Semarang Central Java” aims to determine the types of ancient manuscripts, damage factors, preservation procedures, obstacles encountered, and the appropriateness between theory and application. Methods: This study used a data collection include library research, observation and interviews, while the data processing method uses descriptive analysis. Results and discussion: The results show is a Ranggawarsita Museum Library differentiates its ancient manuscripts into two types: the original manuscript (hand) or in other words, in the form of strips of palm leaf manuscripts, totaling 15 titles and texts that have been experienced over the media in the form of typed writing, totaling 100 titles and the age is 50 years. Damage was generally caused by climatic factors, namely temperature and humidity, pollutant gases, dust and insects. Handling was done by means of preventive measures, curative, control of temperature and humidity, dust, treatment and restoration. Obstacles encountered were environmental conditions near the highway, so a lot of gas pollutants from motor vehicles, the limited budget and space.Conclusion: Applied ancient manuscript conservation activities are in accordance with existing theory that is by controlling the temperature and humidity, dust cleaning, prevention of pollutant gases, insects, preventive measures, curative and restoration. That way the ancient manuscript are still preserved.